Safety and Efficacy of Diode Laser Transscleral Cyclophotocoagulation in Eyes With Good Visual Acuity. Issue 10 (October 2018) - Shah, Parth; Bhakta, Amitabha; Vanner, Elizabeth A.; Kishor, Krishna S.; Greenfield, David S.; Maharaj, Arindel S.R.
Abstract : Background/Aims: The main aim of this study was to evaluate the safety and efficacy of diode laser transscleral cyclophotocoagulation (TSCPC) in eyes with good visual acuity. Patients and Methods: A retrospective chart review identified patients who underwent TSCPC for uncontrolled intraocular pressure (IOP) from 2014 to 2016. Enrollment criteria included pretreatment best-corrected visual acuity (BCVA) of 20 of 40 or better, and a minimum of 6 months of postoperative follow-up. Results: Thirty-three eyes of 33 patients(mean age, 72.1±16.0 y) were enrolled (mean follow-up 12.6±6.1 mo). The mean (SD) IOP was reduced 48.3% from 27.1 mm Hg (7.8) at baseline to 13.1 mm Hg (4.2) at last follow-up. Reduction of ≥1 glaucoma medications was achieved in 17 eyes (51.5%) at last follow-up. The cumulative probability of complete success (BCVA loss <2 Snelling lines, 20% reduction IOP, no reoperation for glaucoma, no IOP<5 mm Hg) was 78.8% and 50% at months 6 and 12, respectively. The cumulative probability of qualified success (BCVA≥2 lines with ≥20% reduction IOP, no reoperation for glaucoma, no IOP<5 mm Hg) was 90.1% and 81.3% at month 6 and 1 year, respectively. Significant vision loss, defined as BCVA≥2 lines, occurred in 33% of patients. The most common complications were postoperative iritic (56.3%) and cystoid macular edema (12.5%). Conclusions: TSCPC demonstrates a strong reduction in IOP and glaucoma medication use. However, with significant vision loss in 33% of patients, future prospective studies with a comparison group receiving traditional glaucoma surgery are needed to determine comparative safety and efficacy.